Plataforma logística para la distribución del Guaviare (2020)
The development of this project begins with the analysis of the Guaviare region, where the most significant problems are analyzed in depth, which generate a progressive decrease in economic, social, cultural and infrastructure growth in general. The main problem is the deficit that the economy presents in the region, which causes that all the other factors of quality of life are poor or directly null, for this reason a master plan is proposed that covers the main themes as objective: (Economic development, Conservation environmental). In San José del Guaviare it is a strategic point to boost the economy through three main projects: (Port, Logistics Platform, Airport), which the focus of this thesis is the logistics platform, which seeks to generate a cargo connection node of merchandise where it receives and distributes adequately, effectively, and above all efficiently, so that the economic development of the region will progressively increase, as well as those of more vital factors in the quality of life of its inhabitants.